A cubic analogue of the RSA cryptosystem - Md Said, Mohamad Rushdan; Loxton, John (Australian Mathematical Publishing Association, 2003)
In this paper, we investigate a public key cryptosystem which is derived from a third order linear recurrence relation and is analogous to the RSA and LUC cryptosystems. The explicit formulation involves a generalisation of the rule for composition of powers and of the calculus of the Euler totient function which underlie the algebra of the RSA cryptosystem. The security of all these systems appears to be comparable and to depend on the intractability of factorisation but the systems do not seem to be mathematically equivalent.